Cutaneous Metastasis from Cholangiocarcinoma Presenting as Thigh Mass - Varma, Kachnar (J Clin Diagn Res, 2016)
Skin is an uncommon site for metastasis with only 0.7-9% of all patients with cancer being affected when compared to other organs. Generally, the time lag between the diagnosis of primary malignancy and the recognition of the skin metastases is long, but sometimes these metastases may be the first indication of otherwise clinically silent visceral malignancies as seen in our case. In cholangiocarcinomas, the occurrence of cutaneous metastases is extremely rare. Their most common sites of metastasis are visceral organs i.e., lungs, bones, adrenal glands and brain. The present case is unique and describes a patient with metastatic cutaneous thigh nodule as the first sign of cholangiocarcinoma. The early recognition of skin metastasis of previously undiagnosed cancers is critical for timely intervention as it indicates poor prognosis with overall survival after cutaneous metastasis of only few months. Very few reports of cutaneous metastases from cholangiocarcinomas have been published. Also, most of these were derived from direct tumour seeding by percutaneous procedures whereas our case showed distant metastasis to thigh. Extensive literature search showed ours to be the first case of cholangiocarcinoma presenting as thigh nodule where Fine Needle Aspiration Cytology (FNAC), histopathology and immunohistochemistry helped in clinching an early diagnosis and judicious management of a patient with unsuspecting thigh nodule.